PENGARUH MEDIA VIDEO YOUTUBE TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA KELAS XI SIMULASI DIGITAL DI SMK NEGERI 1 SUBOH - Dyan Yuliana; Noer Fajri Aminullah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2020)
The low motivation to learn can be seen from the attitudes of students during learning, namely the busyness of students when the teacher explains the lesson, the students are not independently working on the questions given by the teacher, even waiting for answers from their friends or cheating on other students, and the passivity of students when the teacher asks students to come forward to present the results of the group discussion. The low student learning outcomes are explained from the results of daily tests. To obtain data from a number of respondents in order to determine whether there is an effect of the use of YouTube video media on student motivation and learning outcomes using a questionnaire model and learning outcomes test. The data obtained from a qualitative questionnaire was converted into quantitative. The results showed that there was an effect of the use of youtube media on motivation and learning outcomes of class XI students at SMK Negeri 1 Suboh Situbondo in the academic year 2017/2018 with a high level of influence. This can be seen from the value of the correlation coefficient (rcount) of 0.736 at N=30 while the rtabel is 0.361 with a significance level of 5%, which means rcount> rtabel, so there is an effect of youtube media on motivation and student learning outcomes in the subject of Digital Simulation in class X SMK Negeri 1 Suboh 2017/2018 school year.